Chronic disease risk factors associated with health service use in the elderly - Kirkland Susan; Kephart George; Maaten Sarah; Andreou Pantelis (BMC, 2008)
Abstract Background To examine the association between number and combination of chronic disease risk factors on health service use. Methods Data from the 1995 Nova Scotia Health Survey (n = 2,653) was linked to provincial health services administrative databases. Multivariate regression models were developed that included important interactions between risk factors and were stratified by sex and at age 50. Negative-binomial regression models were estimated using generalized estimating equations assuming an autoregressive covariance structure. Results As the number of chronic disease risk factors increased so did the number of annual general practitioner visits, specialist visits and days spent in hospital in people aged 50 and older. This was not seen among individuals under age 50. Comparison of smokers, people with high blood pressure and people with high cholesterol showed no significantly different impact on health service use. Conclusion As the number of chronic disease risk factors increased so did health service use among individuals over age 50 but risk factor combination had no impact.